Hubungan Emotional Dysregulation dengan Kecanduan (Adiksi) Game Online Pada Mahasiswa Laki-laki Universitas Negeri Padang - Rahmayani, Amalia Nuri; Rinaldi, Rinaldi (CAUSALITA : Journal of Psychology, 2024)
This research aims to determine the relationship between emotional dysregulation and online game addiction among male students at Universitas Negeri Padang. The research design used in this study is a correlational quantitative study. The subjects of this study are 250 male students, selected through purposive sampling with the characteristic of playing online games for 12 months (1 year) or more. The instruments used in this study are the Game Addiction Scale (GAS) and the Difficulties in Emotion Regulation Scale (DERS). The data analysis used is Pearson correlation analysis or Product Moment correlation with a correlation value of r = 0.339 and a significance level of p = 0.000 (P < 0.05), which means that H0 is rejected and Ha is accepted. This indicates that there is a relationship between emotional dysregulation and online game addiction among male students at Universitas Negeri Padang.